Management of Strengthening Character Education in Improving Student Attitudes at SDN 231 Sukaasih Bandung - R. Supyan Sauri; Nani Suryani; Siti Hana Adlina Khairunnisa; Aan Puspita (al-Afkar, Journal For Islamic Studies, 2023)
This research is motivated by discussions about character education that are increasingly crowded in Indonesian society. The attitudes and behavior of the people and nation of Indonesia today ignore the noble values that have long been upheld in their daily attitudes and behavior. Noble moral values such as honesty, decency, togetherness and religion are gradually being replaced by foreign cultures where these moral values are no longer considered important. The implementation of character education actually involves all aspects of education, starting from the government as the decision maker for the national education system, leadership, teacher expertise, infrastructure, curriculum and community support. However, teachers have the greatest influence. Teachers must work hard to educate students to become human beings who have character and character. Bandung. Therefore the purpose of this research is to find out the management of strengthening character education in improving students' attitudes at SDN 231 Sukaasih, Bandung City. The use of research methods in this research is qualitative which produces data in descriptive form. Data collection techniques in this study used a combined triangulation method. The results of this study emphasize more on meaning, because it uses qualitative research methods.